Reg en onreg : Kaapse regspraak in die Agtiende Eeu, H.F. Heese : book review (Historia, 2021)
Over the past two decades a renewed interest in the history and nature of early Cape society has emerged in South African historiography. Unlike the earlier "traditional" works the more recent studies do not focus primarily on the white settlers, but are concerned with society-at-large paying particular attention to the San, Khoikhoi and slave communities. In view of the paucity of research material on these sectors of Cape society, the publications that have appeared - and that are still appearing - have had to mainly make use of travellers' accounts, census records ("opgaafrolle") and court cases.
Keywords: Karen Harris; South Africa; Khoikhoi; San; H.F. Heese; Cape; Sentencien; slave society; Afrikaans; Dutch; Europeans; Robert Ross; Wayne Dolling; Anna Böeseken